The Scapegoat - Daphne du Maurier 1907-1989 (UK Penguin Books, 1962)
Two men--one English, the other French--meet by chance in a provincial railway station and are astounded that they are so much alike that they could easily pass for each other. Over the course of a long evening, they talk and drink. It is not until he awakes the next day that John, the Englishman, realizes that he may have spoken too much. His French companion is gone, having stolen his identity. For his part, John has no choice but to take the Frenchman's place--as master of a château, director of a failing business, head of a large and embittered family, and keeper of too many secrets
Keywords: General -- Fiction; Aristocracy (Social class); British -- France -- Fiction